Type 2 Diabetes Mellitus Remission in Patients with Ideal BMI in Rivers State, Nigeria (Global Journal of Medical Research, 2023)
Abstract not found
Keywords: type 2 diabetes; diet; intervention; hba1c; glycaemic control; remission; waist circumference and BMI